Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/jcm11092548
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Superoxide Dismutase, Its Relationship with the Concentration of Zinc and Copper and the Prevalence of rs2070424 Superoxide Dismutase Gene in Women with Polycystic Ovary Syndrome—Preliminary Study

Abstract: Superoxide dismutase (SOD) is a crucial antioxidant enzyme involved in the antioxidant pathway during both normal cellular metabolism and different pathologic processes. We investigated the activity of the copper (Cu)-zinc (Zn) SOD1 as well as the level of Cu and Zn in the serum of women with polycystic ovary syndrome (PCOS) and control group. Moreover, the prevalence of rs2070424 gene polymorphism of the enzyme in the course of PCOS was evaluated. Significantly lower activity of SOD 1 and Cu, Zn concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Significantly lower activity of SOD1 and Cu/Zn concentration were found in a group of women with PCOS compared to control [147]. Insulin resistance in PCOS women causes further decrease in SOD1 activity, while Cu concentration and the value of Cu/Zn was increased when compared to women with normal insulin levels [147]. SOD1 is present in the cytosol, nucleus, peroxisomes, and in small amounts in the mitochondrial membrane of cells and acts to lower the steady-state concentration of O 2…”
Section: Metallic Compounds Proinflammatory Mediators Sod Dysfunction...mentioning
confidence: 77%
See 1 more Smart Citation
“…Significantly lower activity of SOD1 and Cu/Zn concentration were found in a group of women with PCOS compared to control [147]. Insulin resistance in PCOS women causes further decrease in SOD1 activity, while Cu concentration and the value of Cu/Zn was increased when compared to women with normal insulin levels [147]. SOD1 is present in the cytosol, nucleus, peroxisomes, and in small amounts in the mitochondrial membrane of cells and acts to lower the steady-state concentration of O 2…”
Section: Metallic Compounds Proinflammatory Mediators Sod Dysfunction...mentioning
confidence: 77%
“…Two forms of SOD bind to zinc, the first is copper/zinc SOD (CuZnSOD or SOD1), and the second is extracellular SOD (ECSOD or SOD3) which also binds Cu and Zn. Significantly lower activity of SOD1 and Cu/Zn concentration were found in a group of women with PCOS compared to control [147]. Insulin resistance in PCOS women causes further decrease in SOD1 activity, while Cu concentration and the value of Cu/Zn was increased when compared to women with normal insulin levels [147].…”
Section: Metallic Compounds Proinflammatory Mediators Sod Dysfunction...mentioning
confidence: 90%
“…Consequently, controlling Cu in these patients has been recommended as a potential strategy to lower oxidative stress and IR that could be caused by this metal and to minimize long-term metabolic complications [154]. Another study confirmed that patients with PCOS and IR had higher Cu levels than those without IR; however, Cu levels were lower in patients with PCOS than in the control group [165], similar to another work [166]. When Cu levels were measured in the follicular fluid, concentrations were higher in patients with PCOS than in controls [155], and this increase could negatively affect the development of follicles and be related to anomalies in steroidogenesis.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…Consequently, controlling Cu in these patients has been recommended as a potential strategy to lower oxidative stress and IR that could be caused by this metal and to minimize long-term metabolic complications [150]. Another study confirmed that patients with PCOS and IR had higher Cu levels than those without IR; however, Cu levels were lower in patients with PCOS than in the control group [161], similar to another work [162]. When Cu levels were measured in the follicular fluid, concentrations were higher in patients with PCOS than in controls [151], and this increase could negatively affect the development of follicles and be related to anomalies in steroidogenesis.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%

Copper in Gynecological Diseases

Conforti,
Delsouc,
Zorychta
et al. 2023
Preprint